Monetary policy and prudential supervision: From functional separation to a holistic approach? - Matthias Goldmann (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
When prudential supervision was put in the hands of the European Central Bank (ECB), it was the political understanding that the ECB should follow a policy of meticulous separation between monetary policy and financial supervision. However, the financial crisis showed that monetary policy and prudential supervision deeply affect each other and that an overly strict separation might generate systemic risk. As a consequence, the prevalent model of "functional separation" - central banking and financial supervision in separate entities - has been questioned and calls for a more holistic approach increased. This policy letter states that from a legal perspective, such a holistic approach would be in conformity with the current legal framework of the Economic and Monetary Union. Although the realization of a holistic approach might intensify the doubts of democratic legitimation under the framework of the ESCB, the independence of the ECB should not be given up. As viable alternatives to protect monetary policy against the time inconsistency problem that would render central bank independence moot do not seem to be available and given the great importance of the independence of the European institutions for the European integration, the democratic control over the ECB should be strengthened instead of stripping the ECB of its independence.
urn:nbn:de:hebis:30:3-456067
Keywords: 330; monetary policy; financial stability; financial supervision